Mary Harlow and Marie-Louise Nosch (eds). Greek and Roman textiles and dress. An interdisciplinary anthology - Davies, Glenys (Journal of Greek Archaeology, 2016)
The twenty papers in this volume represent a rather diverse set of themes, approaches and types of evidence: the meagre amount of surviving textiles and garments from the Classical world means that in-depth study of what does survive is supplemented by a range of other sources of information, which also need to be used with ingenuity, to expand our knowledge of ancient textiles and dress. Whether or not this can truly be called a coherent discipline (p. 1), it has certainly seen considerable growth in recent scholarship.